Recording and analysing measurements from an RTG crane. (September 2018) - Harrison, I.; Pietrosanti, S.; Luque, A.; Mayer, R.; Holderbaum, W.
Highlights: A novel RTG measurement system design, development and implementation is described. The approach allows for the daily operations of RTGs to be recorded. Measurements taken are at suitable sampling rate to observe inrush currents of drives. A MATLAB based analysis tool has been developed to handle all the measurements. This paper shows the complete path from recording, through analysing to results. Abstract: The paper presents a bespoke power measurement system that has been designed and implemented on a Rubber Tyre Gantry, RTG crane at the Port of Felixstowe, PoF. The design of a novel system topology which is centred around a Beckhoff computer, as well as the specifications of the various transducers used, is detailed. To complement the hardware installation, a bespoke data analysis tool has also been developed in MATLAB, an overview of its operation and use are presented. The system allows for the characterisation of the cranes' various motors during operational hours; furthermore, the data collected has been used to verify simulations of RTGs developed as part of the overall PoF project. The measurement system was installed on RTG1 at the port in March 2016.